On the bilinear covariants associated to mass dimension one spinors - da Silva, J. M. Hoff [UNESP]; Villalobos, C. H. Coronado [UNESP]; Rogerio, R. J. Bueno [UNESP]; Scatena, E. (Springer Nature, 2016)
In this paper we approach the issue of Clifford algebra basis deformation, allowing for bilinear covariants associated to Elko spinors which satisfy the Fierz–Pauli–Kofink identities. We present a complete analysis of covariance, taking into account the involved dual structure associated to Elko spinors. Moreover, the possible generalizations to the recently presented new dual structure are performed.